IMPLEMENTASI KEBIJAKAN PENERTIBAN HEWAN TERNAK DI KECAMATAN BANAWA KABUPATEN DONGGALA - Reza, Mohammad (Katalogis, 2016)
This research is intended to describe the implementation of animal livestock control in Banawa Subdistrict, Donggala Regency. This research was descriptive-qualitative research. The data collection was done through observation, interview, and documentation. The sample of this research was 7 informants selected purposively. The result of research showed that The Implementation of Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency is not optimum yet, because of several aspects influence it, i.e. 1) The objective and the purpose of Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency have been already good. 2) the resources for implementing Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency have not been good. 3) The activity of The Implementation of Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency has not been good yet. 4) The characteristics of the implementer in The Implementation of Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency have not been good yet. 5) The economic, socialÂ and political condition in implementation Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency has been already good. 6) The disposition in implementation Animal Livestock Control Policy in Banawa Subdistrict, Donggala Regency has not been good.